Prevalence, Methicillin Resistance and Inducible Clindamycin Resistance of Staphylococcus aureus Isolated from Retail Ice Cream in Mansoura, Egypt - Omran, Mawadda; Kasem, Nahed G.; Elsherbini, Mohammed; Al-Ashmawy, Maha (Journal of Advanced Veterinary Research, 2023)
Â This work aimed at determination of the prevalence and antimicrobial resistance (AMR) of S. aureus species and investigating the presence of the enterotoxins (SEA and SEB) in the obtained isolates in consumed Egyptian ice cream. Thirty ice cream samples were obtained from many ice cream shops, dairy shops, supermarkets and local markets from different localities at Mansoura city. Samples were spread on Baird Parker selective agar media for bacterial isolation. The isolates were characterized by antibiotic susceptibility testing and resistance genes. S. aureus was detected in 60% (18 out of 30) of ice cream samples with a minimum and maximum count of 4x102 and 1.5x107 CFU/g, respectively. Furthermore, 4 isolates (22%) out of the total isolates (n=18) were positive for nuc gene. Of these positive isolates, one isolate (25%) was positive for mec A and sea genes, while seb was not detected. The AMR profile of molecularly positive nuc gene S. aureus isolates revealed that the highest resistance was against ampicillin, cefazolin, Cefoxitin, cefotaxime, cefepime, azithromycin and amoxycillin- clavulanic acid (100%) followed by gentamicin and erythromycin (75%), and imipenem, tetracycline and clindamycin (50%). No resistance was found to sulphamethazone-trimethoprim, doxycycline, ciprofloxacin, levofloxacin, vancomycin and linezolid. Our results showed that 100% of the molecularly positive nuc gene isolates was methicillin resistant staphylococcus aureus (MRSA) and 50% was inducible clindamycin resistant S. aureus (ICRSA). The MRSA and ICRSA are potential risks for health. Poor hygienic measures with ice cream manufacture may lead to contamination of ice cream with highly resistant enterotoxigenic S. aureus.